Heart transplant outcomes in recipients of Centers for Disease Control (CDC) high risk donors. Issue 12 (23rd October 2016) - Tsiouris, Athanasios; Wilson, Lynn; Sekar, Rajesh B.; Mangi, Abeel A.; Yun, James J.
Abstract: BACKGROUND: A lack of donor hearts remains a major limitation of heart transplantation. Hearts from Centers for Disease Control (CDC) high‐risk donors can be utilized with specific recipient consent. However, outcomes of heart transplantation with CDC high‐risk donors are not well known. We sought to define outcomes, including posttransplant hepatitis and human immunodeficiency virus (HIV) status, in recipients of CDC high‐risk donor hearts at our institution. METHODS: All heart transplant recipients from August 2010 to December 2014 (n = 74) were reviewed. Comparison of 1) CDC high‐risk donor (HRD) versus 2) standard‐risk donor (SRD) groups were performed using chi‐squared tests for nominal data and Wilcoxon two‐sample tests for continuous variables. Survival was estimated with Kaplan‐Meier curves. RESULTS: Of 74 heart transplant recipients reviewed, 66 (89%) received a SRD heart and eight (11%) received a CDC HRD heart. We found no significant differences in recipient age, sex, waiting list 1A status, pretransplant left ventricular assist device (LVAD) support, cytomegalovirus (CMV) status, and graft ischemia times (p = NS) between the HRD and SRD groups. All of the eight HRD were seronegative at the time of transplant. Postoperatively, there was no significant difference in rejection rates at six and 12 months posttransplant. Importantly, no HRD recipients acquired hepatitis or HIV. Survival in HRD versus SRD recipients was not significantly different by Kaplan‐Meier analysis (log rank p = 0.644) at five years posttransplant. CONCLUSION: Heart transplants that were seronegative at the time of transplant had similar posttransplant graft function, rejection rates, and five‐year posttransplant survival versus recipients of SRD hearts. At our institution, no cases of hepatitis or HIV occurred in HRD recipients in early follow‐up.